High-efficiency CO2 separation using hybrid LDH-polymer membranes - Xu, X; Wang, J; Zhou, A; Dong, S; Shi, K; Li, B; Han, J; O'Hare, D (Springer Nature, 2021)
Membrane-based gas separation exhibits many advantages over other conventional techniques; however, the construction of membranes with simultaneous high selectivity and permeability remains a major challenge. Herein, (LDH/FAS)n-PDMS hybrid membranes, containing two-dimensional sub-nanometre channels were fabricated via self-assembly of unilamellar layered double hydroxide (LDH) nanosheets and formamidine sulfinic acid (FAS), followed by spray-coating with a poly(dimethylsiloxane) (PDMS) layer. A CO2 transmission rate for (LDH/FAS)25-PDMS of 7748 GPU together with CO2 selectivity factors (SF) for SF(CO2/H2), SF(CO2/N2) and SF(CO2/CH4) mixtures as high as 43, 86 and 62 respectively are observed. The CO2 permselectivity outperforms most reported systems and is higher than the Robeson or Freeman upper bound limits. These (LDH/FAS)n-PDMS membranes are both thermally and mechanically robust maintaining their highly selective CO2 separation performance during long-term operational testing. We believe this highly-efficient CO2 separation performance is based on the synergy of enhanced solubility, diffusivity and chemical affinity for CO2 in the sub-nanometre channels.